Duration of respiratory events in obstructive sleep apnea: In search of paradoxical results. (April 2023) - Oksenberg, Arie; Leppänen, Timo
Abstract: Research related to the duration of respiratory events in obstructive sleep apnea (OSA) has been scarce, perhaps due to the dominant role played by the apnea-hypopnea index (AHI) in the diagnosis and severity estimation of OSA. Lately, however, researchers and clinicians have started to acknowledge the importance of this overlooked parameter. Intuitively, 40-s-long apneas have more harmful physiological and health consequences than 10-s-long apneas. But is this the case? Here, we review the research-based evidence showing physiological, hemodynamic, clinical, sleep quality, and health consequences of long vs. short respiratory events. Most of the reviewed studies support the idea that longer respiratory events have more severe physiological and clinical consequences than shorter events, most probably due to the higher hypoxic burden associated with longer respiratory events. However, a few but highly qualified studies provide clear evidence that short respiratory events have also a deleterious effect on sleep and the physiological and clinical aspects of OSA. The somewhat paradoxical findings that short respiratory events are also associated with a high risk of all-cause mortality is a serious concern. From these results, it is therefore evident that the duration of respiratory events should be quantified when diagnosing and assessing the severity of OSA.